ANALISIS POTENSI PENERIMAAN NEGARA BUKAN PAJAK SEKTOR PERIKANAN TANGKAP (ANALYSIS THE POTENTIAL OF NON-TAX GOVERNMENT REVENUE FROM FISHERIES SECTOR) - Rita Helbra Tenrini & Anda Nugroho, Agunan P. Samosir (Jurnal Borneo Administrator, 2014)
Realization of non-tax government revenues from fisheries sector since 2006is still far from its potential and actual targets. Though the volume ofproduction from fisheries results tend to research year and in 2012 reached 5.8 million tons and production rate of Rp.72,01trillion. Non-tax government revenues from fisheries in 2012 only amounted about 0.3 percent from the production value of fisheries in Indonesia. Some of region in Indonesia were already experiencing over fishing. If there is no action from the government to control fishing activities, then fisheries sustainability would be threatened. The purpose of this study is to analyze and estimate the potential of non-tax government revenues from fisheries sector. The research method used is a combination of quantitative method (to make analysis about the potential of non-tax government revenues from fisheries sector and its impact to fishers welfare)and qualitative method(to identify problems from every cycle in fisheries management). The results are surprising because of the potential of non-tax government revenues from fisheriesin 2014 could reach 10 times than the realizationin 2012.Keywords: non-tax government revenues, fisheries, fisheries sustainability.Realisasi PNBP sektor Perikanan Tangkap sejak tahun 2006 sampai saat ini masih jauh dari potensi dan target sebenarnya. Padahal volume produksi dari hasil perikanan tangkap cenderung naik setiap tahunnya dan pada tahun 2012 mencapai 5,8 juta ton dan nilai produksinya sebesar Rp72,01 triliun. PNBP Perikanan Tangkap 2012 hanya sebesar 0,3 persen dari nilai produksinya. Beberapa wilayah perikanan di Indonesia sudah mengalami overfishing. Bila tidak ada tindakan dari pemerintah untuk melakukan pengendalian penangkapan ikan, dikhawatirkan akan mengancam keberlangsungan usaha perikanan di Indonesia.Tujuan dari kajian ini adalah menganalisis dan mengestimasi potensi PNBP tahun 2014. Hasil analisis potensi PNBP diharapkan sebagai bahan masukan dalam kebijakan PNBP pada tahun-tahun mendatang. Metode penelitian yang digunakan adalah gabungan antara metode kuantitatif,untuk melakukan analisis besaran potensi perikanan beserta menghitung dampaknya terhadap kesejahteraan nelayan, dan metode kualitatif,untuk mengidentifikasi permasalahan yang ada pada setiap siklus pengelolaan perikanan tangkap.Hasil dari penelitian ini cukup mengejutkan karena potensi PNBP Perikanan tahun 2014 bisa mencapai 10 kali lipat dari realisasi tahun 2012.Kata kunci: Potensi PNBP, sektor perikanan tangkap, Keberlangsungan usaha perikanan